Fundamental Understanding and Application of Ba0.5Sr0.5Co0.8Fe0.2O3−δ Perovskite in Energy Storage and Conversion: Past, Present, and Future - Xu, Xiaomin; Su, Chao; Shao, Zongping (AMER CHEMICAL SOC, 2021)
In the societal pursuit of a carbon-neutral energy future, energy storage and conversion technologies can play a decisive role in better utilizing sustainable energy sources such as wind and solar, in which functional materials that can promote overall energy efficiency hold the key. Perovskite oxides have attracted considerable attention as cost-effective, nonprecious metal-based candidates for this purpose due to their flexible chemistries and tunable physicochemical properties. Of all the perovskite compositions, the barium strontium cobalt iron oxide with a specific chemical formula of Ba0.5Sr0.5Co0.8Fe0.2O3−δ(BSCF) has received considerable and growing interest over the last two decades in a variety of energy applications. In this review, we provide a comprehensive overview of the achievements made on BSCF for various energy storage and conversion applications. Importantly, we offer a fundamental understanding of the roles of BSCF in these applications and of the optimization approaches available to obtain improved functionalities, which can have an enormous impact on the search and development of materials based on BSCF and new materials beyond.